Peran Kantor Urusan Agama dalam Pencegahan Perwalian yang Tidak Berhak: Perspektif Hukum Perkawinan Islam - Delvira, Shania; Firmansyah, Heri (Al-Ishlah: Jurnal Ilmiah Hukum, 2024)
This research aims to examine in depth the process of examining marriage guardian administrative data and the proactive role of the Religious Affairs Office of West Medan Sub-district in preventing unauthorized guardianship. This study combines normative and empirical research methods. Subsequently, the collected data were analyzed qualitatively to describe the problem and address the research purposes. The results show that the Religious Affairs Office of West Medan Sub-district has played a central role in ensuring the legitimacy of marriage guardians through a careful and thorough data examination process and proactive efforts in providing education and outreach to the community. Islamic legal principles, such as amar ma’ruf nahi munkar (enjoining good and forbidding evil), al-’adl (justice), hifz al-nasl (preservation of lineage), maslahah (public interest), and hisbah (accountability), serve as the philosophical and ethical foundations guiding the KUA’s role in maintaining the validity of marriages and protecting the rights of all parties involved. Nevertheless, challenges such as public ignorance, data manipulation, and administrative discrepancies require the KUA to continuously improve the capacity and professionalism of its officers, enhance the data verification system, and strengthen cross-agency coordination. Furthermore, the community must be continuously encouraged to understand the importance of legitimate guardianship and the legal consequences of unauthorized guardianship through intensive and relevant education and outreach programs. Thus, it is hoped that the KUA’s role in preventing unauthorized guardianship can be optimized, creating a more law-abiding and dignified society that upholds noble religious values in every aspect of life, including in marriage, which is the main foundation for building a sakinah, mawaddah, and warahmah (tranquil, loving, and compassionate) family.